PEEP Handout
Peer Education and Equity Programs (PEEP) is a collective ofpeer mentor programs within the Division of AcademicAffairs at CSU Channel Islands. Our common purpose ispeers helping peers to: • navigate college transition, • foster a sense of belonging, • promote engagement in campus culture and high impact practices, • empower peers to make use of student support resources, • and facilitate student success strategies inside and outside of the classroom experience.